A study on the genetic diversity of seven cattle (Bos spp.) Breed population : Genetic Diversity of Seven Cattle Breeds - Hasin, Darimi; Alam, Mohammad Zahangir (Journal of the Sylhet Agricultural University, 2025)
Genetic characteristics are the key to carrying out any modification on an animal to achieve desired goals. Medium-density Bovine SNP chips were used for three hundred and thirteen individuals of seven cattle breeds from secondary sources to study their genetic structure and diversity. The study was carried out from June to September 2021. Different parameters, viz. principal component analysis, minor allele frequency, FIS, FST analysis, admixture analysis, and linkage disequilibrium, were set as the basis of this investigation. Two different versions of PLINK were used to estimate and calculate the diversity parameters. The minor allele frequency in Holstein showed the highest level of genetic diversity, and the lowest was found in Brahman cattle. Heterozygosity was the lowest in Brahman (-0.09), and the highest was in Hanwoo (0.42). Hanwoo and JJBC also showed a significant level of linkage disequilibrium (mean LD was 0.63% and 0.71%, respectively). The FST values showed the most distance between Hereford and Nelore (0.5). The distance between Hanwoo and Holstein was very low (0.07), and the least distance was found between Nelore and Brahman (0.06). Holstein, Hanwoo, and Jeju Black cattle showed minimal admixture in their ancestry. This study revealed a satisfactory genetic history of the seven cattle breeds, which should be insightful for future conservation programs. J. Sylhet Agril. Univ. 12(1): 1-15, 2025